Effects of opium on hippocampal-dependent memory, antioxidant enzyme levels, oxidative stress markers, and histopathological changes of rat hippocampus - Ebrahim Abbasi; Fatemeh Mirzaei; Sodabeh Mashayekhi; Iraj Khodadadi; Alireza Komaki; Nafiseh Faraji; Seyed Alireza Vafaii (Biochemistry and Biophysics Reports)
Background: Opium addiction can affect various organs such as the liver, intestine, kidney, and brain. The hippocampus is one of the brain regions affected early on in Alzheimer's disease and has a vital role in neurogenesis, cognitive function, and memory. This region also is sensitive to oxidative stress and pathophysiological alterations. Hence, this study evaluated the effects of opium on memory and learning, and oxidative stress in the hippocampus of male addicted rats. Since, the hormonal alterations in female arts can affect immune response, metabolism, and behavior, we have selected male rats. Methods: Male rats were randomly divided into two groups: control and opium addicts. Animals received opium (40 mg/kg) for one month. Then, naloxone (2 mg⁄kg), a morphine antagonist, was injected intraperitoneally to confirm addiction. The activities and gene expressions of glutathione peroxidase (GPX), glutathione reductase (GPr), and superoxide dismutase (SOD) were determined by ELISA and Real-time PCR, respectively. Total antioxidant capacity (TAC), total oxidative state (TOS), glutathione, and malondialdehyde (MDA) concentrations, as well as hippocampus histopathology were assessed. Memory and learning were determined by water maze shuttle box tests. Results: The TAC and glutathione levels were decreased, while MDA and TOS increased (P < 0.05) in addicted animals. The gene expressions and activities of GPX, GPr, and SOD decreased in opium-treated animals when compared to control (P < 0.05). Histological analysis showed structural changes in the hippocampal in the opium group. Opium also impaired memory and learning in animals (P < 0.05). Conclusion: Opium consumption has a detrimental effect on hippocampus function and structure.